Physical and mathematical modeling of inclusion removal with gas bottom-blowing in continuous casting tundish - Zhang M.J.; Gu H.Z.; Huang A.; Zhu H.X.; Deng C.J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Gas blowing at the bottom of tundish is an efficient metallurgy technique in clean steelmaking and has been widely concerned. In this paper, spherical alumina particles were selected to model inclusions, 1:3 scale model was utilized, the removal efficiency of inclusions with the gas bottomblowing in the tundish was studied by physical and mathematical modeling. The mathematical model is validated by comparing the predicted and measured residence time distributions and dye flow patterns of tracer. The results show that while the removal efficiency of large size particles has no obvious changes, the gas bottom-blowing has great contribution to the removal of small particles.